الاتجاهات الأممية الجديدة لمفهوم الأسرة _رؤية نقدية من منظور إسلامي - زوانتي بلحسن, بلحسن (University of Eloued جامعة الوادي, 2022)
عد كل من مبدأ المساواة ومبدأ عدم التمييز، من أهم المبادئ التي نالت اهتماما واسعا، ضمن نصوص المواثيق الدولية، وبشكل خاص تلك التي عنيت بحقوق الإنسان، وقد كان لهذين المبدأين دور كبير في تطور مفهوم الأسرة، من مفهومها التقليدي الذي تأسست عليه الأسرة النمطية، إلى مفهوم آخر غير تقليدي أسس لما تسمى الأسرة اللانمطية، وذلك وفق مقاربة خلص من تبناها إلى تفسير موسع للمبدأين مفاده أن المساواة وعدم التمييز ليس مجرد اكتساب لنفس الحقوق وأداء نفس الواجبات بين الرجال والنساء، بل يعني التماثل المطلق بينهما، لدرجة وصف أحدهما ذكرا أو أنثى، يعد بذاته تمييزا مذموما، هذا الطرح يحتاج إلى تقييم من منظور إسلامي، للكشف عن مدى وجاهته. The principle of equality and the principle of non-discrimination are among the most important principles that have received broad attention. In the texts of international instruments, particularly those dealing with human rights.These principles have played a significant role in the evolution of the concept of the family, from its traditional concept on which the stereotypical family is founded, to another non-traditional concept which is the basis of the so-called "atypical family." According to an approach adopted by the sponsors, there is an expanded interpretation of the principles, that equality and non-discrimination are not just the acquisition of the same rights and the performance of the same duties between men and women, but the absolute uniformity between them. To the point of describing one male or female as a self-declared distinction, this proposition needs to be evaluated from an Islamic perspective to reveal its relevance.
المجلد13 العدد2
Keywords: أسرة ; عدم التمييز ; جندر ; حركة نسائية ; أمم متحدة ; شريعة إسلامية; Keywords: family ; Non-discrimination ; gender; women's movement; United Nations